Baicalin-aluminum alleviates necrotic enteritis in broiler chickens by inhibiting virulence factors expression of Clostridium perfringens - Liu, Jin; Wu, Shuangqi; Zhao, Honghao; Ye, Chun; Fu, Shulin; Liu, Yu; Liu, Ting; Qiu, Yinsheng (Frontiers in Cellular and Infection Microbiology, 2023)
Clostridium perfringens type A is the main cause of necrotic enteritis (NE) in chickens. Since the use of antibiotics in feed is withdrawn, it is imperative to find out suitable alternatives to control NE. Baicalin-aluminum complex is synthesized from baicalin, a flavonoid isolated from Scutellaria baicalensis Georgi. The present study investigated the effects of baicalin-aluminum on the virulence-associated traits and virulence genes expression of C. perfringens CVCC2030, it also evaluated the in vivo therapeutic effect on NE. The results showed that baicalin-aluminum inhibited bacterial hemolytic activity, diminished biofilm formation, attenuated cytotoxicity to Caco-2 cells, downregulated the expression of genes encoding for clostridial toxins and extracellular enzymes such as alpha toxin (CPA), perfringolysin O (PFO), collagenase (ColA), and sialidases (NanI, NanJ). Additionally, baicalin-aluminum was found to negatively regulate the expression of genes involved in quorum sensing (QS) communication, including genes of Agr QS system (agrB, agrD) and genes of VirS/R two-component regulatory system (virS, virR). In vivo experiments, baicalinaluminum lightened the intestinal lesions and histological damage, it inhibited proinflammatory cytokines (TNF-α, IL-1β, IL-6) expression in the jejunal and ileal tissues. Besides, baicalin-aluminum alleviated the upregulation of C. perfringens and Escherichia coli and raised the relative abundance of Lactobacillus in the ileal digesta.This study suggests that baicalin-aluminum may be a potential candidate against C. perfringens infection by inhibiting the virulence-associated traits and virulence genes expression.